2019
DOI: 10.1038/s41598-019-51275-w
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of tobacco use in residents of hilly areas and foot hills of Western Ghats, Southern India

Abstract: Smoking and smokeless tobacco consumption is a significant risk factor that provokes genetic alterations. The present investigation was to evaluate the biomarkers of genotoxicity including micronucleus (MN), chromosome aberrations (CA) and DNA strand breaks among tobacco consumers and control individuals residing in hilly areas of Western Ghats, Tamilnadu, South India. This study included 268 tobacco consumers with equal number of controls. The tobacco consumers were divided into Group I (<10 years of tobacco … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
(40 reference statements)
3
7
0
Order By: Relevance
“…A possible explanation for this can be the young age of the participants, the relative decreased number of package-years in the group of conventional smokers and the fact that exfoliative cytology can sometimes underestimate the MN count due to the time needed for the migration of cells from basal to superficial layers of the oral epithelium. We found that more cells showing MN were present in specimens from smokers and e-cigarettes users compared with nonsmokers, similar to data reported by other studies [29,43]. Furthermore, a systematic review of clinical studies published in 2018 found a higher frequency of MN in exfoliated cells of smokers compared to non-smokers and concluded that this is associated with cytotoxic and genotoxic effects [44].…”
Section: Discussionsupporting
confidence: 89%
“…A possible explanation for this can be the young age of the participants, the relative decreased number of package-years in the group of conventional smokers and the fact that exfoliative cytology can sometimes underestimate the MN count due to the time needed for the migration of cells from basal to superficial layers of the oral epithelium. We found that more cells showing MN were present in specimens from smokers and e-cigarettes users compared with nonsmokers, similar to data reported by other studies [29,43]. Furthermore, a systematic review of clinical studies published in 2018 found a higher frequency of MN in exfoliated cells of smokers compared to non-smokers and concluded that this is associated with cytotoxic and genotoxic effects [44].…”
Section: Discussionsupporting
confidence: 89%
“…We also found that frequency of cells showing micronuclei was significantly increased in combined tobacco users when compared with other groups. Similar findings were observed by (Upadhyay et al, 2019;Chandirasekar et al, 2019). The micronuclei related genotoxic alterations in the cells may be due to the possibility that the buccal mucosa cells get direct exposure to the carcinogenic amines present in the tobacco (Proia et al, 2006).…”
Section: Discussionsupporting
confidence: 84%
“…The effect of smoking on DNA damage has been thoroughly studied, mainly as a confounding factor in biomonitoring studies addressing exposure to other compounds (68,69). Despite that, discrepant results have been reported in the literature, either describing a lack of association between smoking and DNA damage induction (the majority of studies), as reviewed elsewhere (68)(69)(70) or an increased DNA damage in smokers comparatively to non-smokers (37,38,(71)(72)(73)(74). Very few studies have been published in respect to the effect of ETS exposure on this biomarker and contradictory results have been reported.…”
Section: Discussionmentioning
confidence: 99%